Optical, water splitting and wettability of titanium nitride/titanium oxynitride bilayer films for hydrogen generation and solar cells applications. (January 2020) - Mohamed, S.H.; Zhao, Huaping; Romanus, Henry; El-Hossary, F.M.; Abo EL-Kassem, M.; Awad, M.A.; Rabia, Mohamed; Lei, Yong
Abstract: TiN/TiOx Ny bilayer films with various TiN thicknesses were prepared using direct current (d.c.) reactive magnetron sputtering. The ratio of N/O in the bilayer films increased with increasing TiN top layer thickness. The observed crystalline peaks for the bilayer films, for different TiN layer thicknesses, were indexed to anatase TiO2 with tetragonal structure. Only 0.31° peak shift, to lower 2θ angles was detected. FESEM indicated that the morphology of TiOx Ny single layer is consisted of elongated nanocrystals with diameters in the range of 27.9–46.8 nm and the diameters of the nanocrystallites changed slightly with increasing the thickness of TiN layer. The transmittance, absorbance, reflectance spectra and the optical constants of the bilayer films were presented. The photoelectrochemical performance for water splitting of TiN/TiOx Ny bilayer films was studied by examination both the continuous and chopped photocurrent density under light illumination. The photocurrent density increases with increasing TiN top layer up to a thickness of 9 nm, after which a reduction in photocurrent is observed. The wettability of TiN/TiOx Ny bilayer films could be transformed by UV illumination from hydrophobic to hydrophilic.